Heavy metal exposure assessment using nail as bio-indicator among the farmers in Malaysia - Yew, Yee Shien (2015)
Heavy metals, particularly cadmium, lead, and arsenic, constitute a significant potential threat to human health. Chronic exposure to toxic heavy metal can lead to deleterious human health effect. The aim of this study was to determine the level of heavy metal concentration among the farmers in Malaysia as well as to understand the correlation between the heavy metal levels with the heavy metal sensitivity symptoms. The study comprised of 33 farmers. Nails sample was collected among the farmers and the adopted questionnaire were used to obtained demographic status and related symptoms. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze the nail sample and the Statistical Package for Social Sciences (SPSS) were used to analyze the data obtained In this study, there were significant correlations between the working experiences with level of arsenic, cadmium, nickel and lead, (r=0.499, r=0.398, r-0.454, r0.498., p <0.05). Besides, the analysis of the relationship between the age and levels of arsenic (r0.499), cadmium (r0.398), nickel (r=0.454), and lead (r0.498), (p <0.05) showed significant relationship. This finding suggests that agriculture activities could contribute to the accumulations of heavy metals in farmers. Hence, the control of environmental levels of and human exposure to these metals to prevent adverse health effects is still an important public health issue.